Anionic Mixture supplementation and their impact on hemato-biochemical parameters and post partum performance of buffaloes under field conditions: Impact of anionic mixture supplementation on hemato-biochemical parameters and post partum performance of buffaloes - Sohan Vir Singh, Gaurav Kumar and Rajkumar (Indian Journal of Dairy Science, 2024)
In order to demonstrate the beneficial effect of anionic mixture supplementation to the famers, advanced pregnant (nine months) Murrah buffaloes were selected from adopted village (Kathura, Distt. Sonipat) under Farmer FIRST project. Experimental animals were supplementing anionic mixture (@100gm/day/head) from 21 days before expected date of parturition.  Blood samples were collected from the control and experimental group of animals at the start of supplementation of the anionic mixture and after 21 days of parturition. Blood samples were analyzed for hematological and biochemical parameters. Experimental animals were also monitored for the udder development, milk fever, retention of placenta and body condition. The overall mean values of liver enzymes i.e. ALT, AST  were numerically lower while the mean values of total protein, Albumin, Globulin, Triglyceride and Potassium were higher during postpartum compared to prepartum period in supplemented than control group. The overall mean values of hematological parameters (Hb and PCV) were found significantly (P